A Clinical Monitoring Program of COVID-19 Outpatients: A Prospective Cohort Study. (20th July 2021) - Kasiri, Hossein; Mahjub, Cyrus; Mazaeri, Mohammadreza; Naderi-Behdani, Fahimeh; Bazi, Aliyeh; Ghazaeian, Monireh; Fallah, Sahar
Abstract : Purpose . Coronavirus disease 2019 (COVID-19) has been associated with a high rate of mortality and morbidity. While a high portion of COVID-19 patients have mild symptoms, a limited number of clinical trials have evaluated the clinical course of this large group of patients. This study was designed to investigate the demographics and clinical characteristics and comorbidity of nonhospitalized COVID-19 patients. Methods . This prospective, observational cohort study was performed on nonhospitalized adult patients (≥18 years) with COVID-19. Pharmacotherapy service was responsible for patients' assessment for up to 1 month. Demographic characteristics, the onset of symptoms, severity, duration, laboratory data, and hospitalization rate were evaluated by a pharmacist-based monitoring program. Results . From 323 patients who had been referred to the emergency department, 105 individuals were recruited between April 26 and August 2, 2020. Most of the patients were female (66.7%) with a mean age of 39.39 years (SD: ± 15.82). The mean time of the symptom onset was 5.6 days (SD: ±1.79). The majority of patients suffered from fatigue (78.1%), sore throat (67.6%), cough (60%), and myalgia (55.2%). C-reactive protein, white blood cell, lymphocyte, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and hemoglobin levels were recovered significantly during the first two weeks (P < 0.001 ). Hydroxychloroquine, naproxen, diphenhydramine, azithromycin, and vitamin D3 were the most common medications administered (98%, 96%, 94%, 68%, and 57%, respectively). Forty patients were not symptom-free after the one-month follow-up, and 8 patients (7.6%) were required to revisit without the need for hospitalization. Anosmia (18.1%) and fatigue (17.1%) were the most common persisted symptoms. There were no significant differences between symptom-free and symptomatic patients. Conclusion . Mild COVID-19 patients had a wide variety of symptoms and could be symptomatic even one month after the onset of symptoms. The pharmacist-based monitoring system can contribute beneficially to patients through the evaluation of symptoms, reduction of unnecessary visits, and provision of updated information to patients concerning the status of their illness.